ANALISIS PENERAPAN TEKNIK SKIMMING TERHADAP OPTIMALISASI PEMAHAMAN BACAAN MAHASISWA STKIP MUHAMMADIYAH MUARA BUNGO - yulia oktarina (LP3M Universitas Muhammadiyah Muara Bungo, 2019)
This study aims to analyze the application of skimming techniques to the optimal reading comprehension on students of STKIP MB. This research uses a quantitative approach with quasi-experimental and descriptive research. This research was conducted on students of STKIP MB Academic Year 2018/2019. The conclusions of this study include: (1) the level of reading comprehension after applying skimming techniques is better than the reading comprehension level before applying skimming techniques performed on the same research subject, (3) the level of reading comprehension by applying skimming techniques is better than the reading comprehension level by applying conventional reading conducted on different research subjects. So, reading with skimming techniques has a significant effect on optimizing students' reading comprehension.